2012
DOI: 10.1186/1746-1596-7-147
|View full text |Cite
|
Sign up to set email alerts
|

Genomic amplification of the human telomerase gene (hTERC) associated with human papillomavirus is related to the progression of uterine cervical dysplasia to invasive cancer

Abstract: BackgroundHuman papillomavirus (HPV) infection plays an etiological role in the development of cervical dysplasia and cancer. Amplification of human telomerase gene (hTERC) and over expression of telomerase were found to be associated with cervical tumorigenesis. This study was performed to analyze genomic amplification of hTERC gene, telomerase activity in association with HPV infection in different stages of cervical intraepithelial neoplasia (CIN) and cervical cancer. We were studying the role of hTERC in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 22 publications
7
35
0
Order By: Relevance
“…The clearance rate of drug mostly depends on metabolic activity in vivo biotransformation process [3, 22]. To further confirm Ary's anticancer effect in vivo , Hela cells were transplanted in nude mice.…”
Section: Resultsmentioning
confidence: 99%
“…The clearance rate of drug mostly depends on metabolic activity in vivo biotransformation process [3, 22]. To further confirm Ary's anticancer effect in vivo , Hela cells were transplanted in nude mice.…”
Section: Resultsmentioning
confidence: 99%
“…Hongqian et al showed the Potential clinical usefulness of the hTERC FISH in distinguishing patients with clinically significant cervical lesions from those that are insignificant lesions, especially in HPV-infection patients [18]. …”
Section: Discussionmentioning
confidence: 99%
“…Currently, new methods have been implicated. Liu et al [3] applied the genomic amplification of the human telomerase gene (hTERC) as a supplementary method to screen cervical cancer in high-risk patients. For the detection of high-grade cervical intraepithelial neoplasia (CIN), Chen et al [4] used the genomic amplification patterns of human telomerase RNA gene and C-MYC.…”
Section: Introductionmentioning
confidence: 99%